Facilitating Research in Physician Assistant Programs: Creating a Student-Level Longitudinal Database. Issue 3 (September 2015) - Morgan, Perri; Humeniuk, Katherine M.; Everett, Christine M.
Abstract : Abstract: As physician assistant (PA) roles expand and diversify in the United States and around the world, there is a pressing need for research that illuminates how PAs may best be selected, educated, and used in health systems to maximize their potential contributions to health. Physician assistant education programs are well positioned to advance this research by collecting and organizing data on applicants, students, and graduates. Our PA program is creating a permanent longitudinal education database for research that contains extensive student-level data. This database will allow us to conduct research on all phases of PA education, from admission processes through the professional practice of our graduates. In this article, we describe our approach to constructing a longitudinal student-level research database and discuss the strengths and limitations of longitudinal databases for research on education and the practice of PAs. We hope to encourage other PA programs to initiate similar projects so that, in the future, data can be combined for use in multi-institutional research that can contribute to improved education for PA students across programs.